2020
DOI: 10.3324/haematol.2020.262121
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation therapy of myeloid leukemia: four decades of development

Abstract: Acute myeloid leukemia is characterized by arrested differentiation, and agents that overcome this block are therapeutically useful, as shown by the efficacy of all-trans retinoic acid in acute promyelocytic leukemia. However, the early promise of differentiation therapy did not translate into clinical benefit for other subtypes of acute myeloid leukemia, in which cytotoxic chemotherapeutic regimens remained the standard of care. Recent advances, including insights from sequencing of acute myeloid leukemia gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 133 publications
(168 reference statements)
2
49
0
Order By: Relevance
“…Differentiation therapy has been considered a promising approach for the treatment of AML for several decades, inspired by the tremendous effect of all- trans retinoic acid (ATRA) in the treatment of acute promyelocytic leukemia, as well as the extensive biological effects in acute myeloid leukemia cells in general [ 20 ]. However, despite the encouraging effects of several differentiation inducing agents like valproic acid (VPA) and ATRA alone and in combination in cellular models, clinical efficacy in non-acute promyelocytic leukemia remains moderate [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Differentiation therapy has been considered a promising approach for the treatment of AML for several decades, inspired by the tremendous effect of all- trans retinoic acid (ATRA) in the treatment of acute promyelocytic leukemia, as well as the extensive biological effects in acute myeloid leukemia cells in general [ 20 ]. However, despite the encouraging effects of several differentiation inducing agents like valproic acid (VPA) and ATRA alone and in combination in cellular models, clinical efficacy in non-acute promyelocytic leukemia remains moderate [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…AML is characterized by a differentiation block leading to accumulation of highly proliferative immature myeloid blasts. Therefore, differentiation-based therapy is a promising approach for AML treatment [ 41 ]. We have previously shown that (pro-)electrophilic polyphenols and drugs can enhance monocyte/macrophage differentiation of AML cells triggered by active vitamin D derivatives or other agents, without inducing cytotoxicity [ 24 , 25 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Connecting glucose uptake indirectly to activation of epigenetic enzymes with dual activity, in AML, LSD1 stabilises the transcription factor GATA1 on protein level and epigenetically silences the GATA1 negative regulator C/EBPα, thus promoting glucose metabolism [ 323 ]. In haematological malignancies, e.g., AML, MDS, and CML, LSD1 contributes to leukaemogenesis [ 324 ].…”
Section: The Teamwork Between Epigenetics and Metabolism In Haematological Malignanciesmentioning
confidence: 99%